A Recombinant Porcine Reproductive and Respiratory Syndrome Virus Stably Expressing DsRed Protein Based on Bacterial Artificial Chromosome System - Li, Na; Zhang, Yiyi; Yao, Lunguang; Shi, Yunpeng; Zhao, Qin; Huang, Baicheng; Sun, Yani (Frontiers in Microbiology, 2022)
Recombinant viruses possessing reporter proteins as tools are widely applied in investigating viral biology because of the convenience for observation. Previously, we generated a recombinant pathogenic porcine reproductive and respiratory syndrome virus (PRRSV) with enhanced green fluorescent protein (EGFP) reporter for monitoring virus spread and screening of neutralizing antibodies. PRRSV with different kinds of reporters can support more application scenarios. Here, we described a new genetically stable infectious clones of a highly pathogenic PRRSV (HP-PRRSV) harboring the DsRed (a red fluorescent protein isolated from the coral Discosoma) gene. In the recombinant infectious clone, the transcription regulatory sequence 2 (TRS2) of PRRSV was inserted between the open reading frame 7 (ORF7) and 3’UTR to drive the transcription of DsRed gene, which makes it a separate transcription unit in the viral genome. Using the bacterial artificial chromosome (BAC) system and cytomegalovirus (CMV) promoter, the recombinant HP-PRRSV with the DsRed insertion was successfully rescued and showed similar growth and replication patterns compared with the wild-type virus in the MARC-145 cells. In addition, the DsRed protein was stably expressed in the recombinant virus for at least 10 passages with consistent fluorescence intensity and density. Using the recombinant HP-PRRSV with DsRed protein, the virus tracking in MARC-145 was observed by live-cell imaging. Meanwhile, quantification of the DsRed fluorescence positive cells by flow cytometry provides an alternative to standard methods for testing the level of PRRSV infection. This recombinant PRRSV with DsRed fluorescence protein expression could be a useful tool for fundamental research on the viral biology and shows the new design for stable expression of foreign genes in PRRSV.